(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The perspective of the analog and digital technology realty will encourage new forms of creation and the exercise of the rights of works which are protected by intellectual property rights and at the same time it can break the security systems on them. In the Information Society the enjoyment of works is already international, leading to harmonize rules on copyright and other related rights, recognizing similar criteria in the States that enables compatibility in implementing their legal systems. In the European Community (EC) it is possible to highlight two points that guide an effective protection of copyright in the Information Society: Directive 2001/29/EC of the European Parliament and Council on the harmonization of certain aspects of copyright and rights related to copyright in the Information Society (DDASI) and the recent “Green Paper on Copyright in the Knowledge Economy” published by the European Commission on July 16, 2008. While in Spain the transposition of Directive 2001/29/EC will be reflected by Law 23/2006 of July 7, amendingTRLPI 1996, and the regulation of digital private copy retribution in the OrderPRE/1743/2008 of June 18.